Out-put Characteristics of Low Power He-Ne Laser Efficiency Determination - Gullala. Y. Baker (Zanco Journal of Pure and Applied Sciences, 2021)
It is known that any laser has a pumping source, an amplifying medium and a resonator that oscillates the active mode representing the out-put wavelength of the laser. The suitable value for this ratio is 7:1 He/Ne in volume. These were to prepare under an ideal mixture of these gases as treated before by many experiment lists. The aim of this study to specify is to the basic portions of low power He-Ne gas lasers available in laboratories, and to test them in order to look for a probable factor of the efficiency as the whole. All calculations were performed, using calculators. The results were unique for all of them that the laser aperture also plays an important role in this criteria. The best fitting ratio between the radius of laser aperture and that of laser beam was determined and connected to the other parts of the efficiency, also the ratio of(ρ/ω) was fixed at 1.55.